Perception of Musharakah Mutanaqisah system in home financing among lecturers of ACIS in UiTM Puncak Alam / Nurzahirah Nasir - Nasir, Nurzahirah (2019)
The lack of knowledge about Islamic home financing is becoming a growing concern. The problem of society nowadays are they prefer to choose the conventional rather the Islamic. There is an urgent need for innovation, for better understanding about the concept of Islamic home financing. Thus, various innovations need to be done to expose the community to the benefits of using Islamic home financing. Thus, the objectives of this research are to know the concept of Musharakah Mutanaqisah system and conventional loan, to study the comparison between Musharakah Mutanaqisah system and conventional loan and lastly is to describe the impact of Musharakah Mutanaqisah to society . It specifically studies on UiTM Puncak Alam. There are 17 respondents that participate in this research where all the respondents are staffs at MARA University of Technology Malaysia, Puncak Alam.This research analysing by using manual method. From the finding it can be said that the concept of Islamic home financing have many advantages compared to the conventional. Islamic home financing is suitable to use for all society include non-Muslim because of it easier and have many advantages. It is also suggested that holistic strategic approach is needed for expose to society about the advantages of using Islamic home financing. It is hope that the study can contribute to the implement of Islamic home financing in society.